2022
DOI: 10.1039/d1cp05466j
|View full text |Cite
|
Sign up to set email alerts
|

Construction of stable MoxSy/CeO2 heterostructures for the electrocatalytic hydrogen evolution reaction

Abstract: The unique structures of polynuclear MoxSy clusters make them maximize the number of active sites, being good candidates as HER catalysts. An appropriate support is highly necessary not only to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…1), including Nb 3 S 4 , Nb 4 S 3 , and Nb 4 S 4 clusters. 29 Three Nb atoms of incomplete cubane-type Nb 3 S 4 clusters constructed an isosceles triangle with an average bond length ( l Nb–Nb ) of 2.57 Å, and the coordination structures of S atoms included three doubly bridging sulfurs (μ 2 -S) and one triply-bridging sulfur (μ 3 -S), where the average value of l Nb–(μ 2 -S) and l Nb–(μ 3 -S) were 2.37 Å and 2.45 Å, respectively. The Nb atoms of Nb 4 S 3 formed a regular triangular pyramid coordinated with three μ 2 -S, and the skeleton structure of Nb 4 S 4 was an Nb 4 tetrahedron with four μ 3 -S. The values of the bottom and side l Nb–Nb on Nb 4 S 3 were 2.61 Å and 2.68 Å, respectively, and the l Nb–Nb of Nb 4 S 4 was shorter with a value of 2.58 Å.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1), including Nb 3 S 4 , Nb 4 S 3 , and Nb 4 S 4 clusters. 29 Three Nb atoms of incomplete cubane-type Nb 3 S 4 clusters constructed an isosceles triangle with an average bond length ( l Nb–Nb ) of 2.57 Å, and the coordination structures of S atoms included three doubly bridging sulfurs (μ 2 -S) and one triply-bridging sulfur (μ 3 -S), where the average value of l Nb–(μ 2 -S) and l Nb–(μ 3 -S) were 2.37 Å and 2.45 Å, respectively. The Nb atoms of Nb 4 S 3 formed a regular triangular pyramid coordinated with three μ 2 -S, and the skeleton structure of Nb 4 S 4 was an Nb 4 tetrahedron with four μ 3 -S. The values of the bottom and side l Nb–Nb on Nb 4 S 3 were 2.61 Å and 2.68 Å, respectively, and the l Nb–Nb of Nb 4 S 4 was shorter with a value of 2.58 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The Bader charge transfer (Dq) from Nb 3 S 4 , Nb 4 S 3 , and Nb 4 S 4 to CeO 2 supports are 1.29e, 1.55e, and 1.09e, respectively, which means that these Nb x S y clusters are positively charged, accompanying the reduction of some Ce atoms from Ce 4+ to Ce 3+ . 29 From the Bader charge shown in Table S2, † we can see that the reduced Ce 3+ cations are negatively charged with ∼0.30e compared with the inner-layer Ce 4+ , showing the injection of the electrons to these reduced Ce 3+ cations. Compared with 0 m B of Ce 4+ , the Ce-4f orbitals of the reduced Ce 3+ cations would present a magnetic moment of ∼1 m B due to the electron injection (Table S2 †).…”
Section: Electronic Structures and Reaction Mechanisms Of The Absorbe...mentioning
confidence: 94%
See 2 more Smart Citations
“…The research by Zhang et al showed that CeO 2 support can provide strong support for the interaction of various Mo x S y clusters, and the formed Mo x S y /CeO 2 heterostructures also have moderate Δ G H* for the HER. 107 The electronic properties of Mo x S y clusters are regulated by CeO 2 carriers, which cause charge redistribution on the edge atoms and play a key role in H adsorption. This study provides guidance for the prediction of highly effective candidate MoS 2 based catalysts for the HER.…”
Section: Electrochemical Applicationsmentioning
confidence: 99%